Hollow Microneedle Arrays Produced by Low‐Cost, High‐Fidelity Replication of Hypodermic Needle Tips for High‐Dose Transdermal Drug Delivery. Issue 6 (24th June 2021) - Zhou, Cuiping; Tang, Hao; Zhang, Li; An, Hong; Wu, Yunjin; Tang, Ding; Zhou, Jianhua
Abstract : Hollow microneedle arrays (HMN), which exhibit advantages like safety in use, painlessness, high drug loading, precise administration and convenience of connecting to external devices, have been massively produced via a simple, low‐cost and high‐fidelity replication strategy. The as‐obtained HMN could be integrated onto a microfluidic chip with different microchannels, and the microfluidic chip could be further applied to fabricate a bundle device by attaching the chip to a looped zip tie. By using this zip tie, vaccines or drugs could be loaded in a convenient way, as described in the article, number 2001355, by Jianhua Zhou and co‐workers.